Relationship between serum bicarbonate levels and the risk of death within 30 days in ICU patients with acute ischemic stroke - Huang, Xia; Zhang, Yuanyuan (Frontiers in Neurology, 2023)
Aim: To explore the associations of baseline bicarbonate levels and their changes with 30-day mortality in patients with acute ischemic stroke who admitted to intensive care unit (ICU). Methods: This cohort study collected the data of 4,048 participants from Medical Information Mart for Intensive Care (MIMIC)-III and MIMIC-IV database. Univariate and multivariable Cox proportional risk models were utilized to explore the associations of bicarbonate T0 and Δbicarbonate with 30-day mortality in patients with acute ischemic stroke. Kaplan-Meier curves were plotted to measure the 30-day survival probability of patients with acute ischemic stroke. Results: The median follow-up time was 30.00 days. At the end of the follow-up, 3,172 patients survived. Bicarbonate T0 ≤21 mEq/L [hazard ratio (HR)=1.24, 95% confidence interval (CI): 1.02-1.50] or 21 mEq/L 26 mEq/L. -2 mEq/L <Δbicarbonate ≤0 mEq/L (HR=1.40, 95%CI: 1.14-1.71), 0 mEq/L<Δbicarbonate ≤2 mEq/L (HR=1.44, 95%CI: 1.17-1.76) and Δbicarbonate >2 mEq/L (HR=1.40, 95%CI: 1.15-1.71) were correlated with elevated risk of 30-day mortality in acute ischemic stroke patients. The 30-day survival probability of acute ischemic stroke patients with 21 mEq/L 26 mEq/L was higher than those with bicarbonate T0 ≤21 mEq/L. The 30-day survival probability in patients with Δbicarbonate ≤-2 mEq/L group was higher than higher than those with Δbicarbonate >2 mEq/L. Conclusion: Low baseline bicarbonate level and decreased bicarbonate level during ICU stay were associated with high risk of 30-day mortality in acute ischemic stroke. Special interventions should be offered to those with low baseline bicarbonate level and decreased bicarbonate level during ICU stay.